On H-irregular reflexive labeling of graph - Marsidi, Marsidi; Agustin, Ika Hesti; Dafik, Dafik; Rahman, Md. Saidur; Sullystiawati, Lusia Herni (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
By an irregular reflexive labeling, we mean a function and such that if and if , where max . Let , the irregular reflexive labeling is called an -irregular reflexive -labeling of graph if every two different sub graphs and isomorphic to , it holds , where . The minimum for graph which has an -irregular reflexive -labeling is called the reflexive strength of graph and denoted by . In this paper we initiate to study the lower bound of the reflexive strenght of graphs and the reflexive strenght of flower, Shack and book graph, where isomorphic to and , respectively.